2010
DOI: 10.1002/adfm.200902013
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of CdSe‐Nanofibers with Potential for Biomedical Applications

Abstract: The design and synthesis of nanostructured functional hybrid biomaterials are essential for the next generation of advanced diagnostics and the treatment of disease. A simple route to fabricate semiconductor nanofibers by self‐assembled, elastin‐like polymer (ELP)‐templated semiconductor nanoparticles is reported. Core–shell nanostructures of CdSe nanoparticles with a shell of ELPs are used as building blocks to fabricate functional one‐dimensional (1D) nanostructures. The CdSe particles are generated in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…The ELR stabilizes the CdSe nanoparticles in an aqueous medium and controls their nucleation, growth and spatial distribution, thus leading to the selfassembly of core-shell building blocks into fibril architectures. The use of nontoxic nanofibrous materials has shown that the combination of different materials with ELRs is a promising strategy to find new applications in fields such as medical nanotechnology and the diagnosis and treatment of various diseases [59].…”
Section: Elrsmentioning
confidence: 99%
“…The ELR stabilizes the CdSe nanoparticles in an aqueous medium and controls their nucleation, growth and spatial distribution, thus leading to the selfassembly of core-shell building blocks into fibril architectures. The use of nontoxic nanofibrous materials has shown that the combination of different materials with ELRs is a promising strategy to find new applications in fields such as medical nanotechnology and the diagnosis and treatment of various diseases [59].…”
Section: Elrsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Consequently, to synthesize hierarchical inorganic crystals or hybrid inorganic-organic materials with controlled size and morphology has been an intensive focus, owing to the importance and potential to design new materials and devices in various fields such as medicine, ceramics, catalysis and cosmetics. [7][8][9][10][11][12][13][14][15] In these researches, the fundamental understanding of the formation processes of crystals or inorganicorganic hybrids is also very important and could affect many practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…3 Also spherical nanoparticles can form 1D structures via self-assembly and show promising properties for biomedical applications. 4 Fibroid structures can be applied to diverse purposes, for example water purification by nano-fibrous membranes made of polysaccharide. 5 Nevertheless, the production of 1D structures is rather challenging, as shape, size and monodispersity have to be controlled.…”
Section: Introductionmentioning
confidence: 99%